Beyond Data Capture: A Single Institutional Experience with Establishing a Pelvic Floor Surgery Web Based Database. Issue 2 (27th March 2020) - Lee, Wai; Du, Chris; Choe, Chong; Massman, John D.; Kim, Jason; Lee, Una J.; Lucioni, Alvaro; Kobashi, Kathleen C.
Abstract: Introduction: The American Urological Association has highlighted the need for complete and long-term data collection in female pelvic medicine and reconstructive surgery. We describe our institution's experience with transitioning our pelvic floor surgery database to a secure web based platform. In this article we share this experience and its challenges to help facilitate the process for other institutions. Methods: In 1999 our institution implemented electronic data capture of pelvic floor cases using a stand-alone spreadsheet. By 2001 it was apparent that this modality could no longer sustain growth while maintaining data integrity. We converted to a relational database system but limitations involving multiuser data entry and efficient querying became apparent. After consultation with outcomes research experts across the country we evaluated database alternatives for capacity, ease of use and security. REDCap® (Research Electronic Data Capture), a low cost, server based database software, provided all 3. Results: In 2011 the transition of our electronic outcomes database to REDCap commenced. The transition required approximately 100 person-hours for data dictionary creation and 200 person-hours for the transfer of existing data into REDCap. A database administrator was hired to maintain data integrity, automate the process of generating questionnaires for long-term followup and facilitate data queries. Conclusions: We describe the transition of our institution's outcomes database to REDCap providing the means for secure and streamlined data capture and quality assurance. This platform also facilitates effective multi-institutional collaboration with the goals of developing quality data to advance research and improve care for our patients.